A method for preparing super cross-linked polyaniline by N-alkylation reaction
By performing the N-alkylation reaction with hollow spherical polyaniline and oxalyl chloride, supercrosslinked polyaniline with high thermal stability and good adsorption properties was prepared, which solved the problems of high preparation cost and poor chemical stability in the prior art, and achieved a low-cost and efficient preparation process.
Patent Information
- Application Number
- CN202210624705.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-02
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-06-02
AI Technical Summary
The existing preparation methods for supercrosslinked polyaniline have problems such as high reaction temperature, complex reaction operation, long reaction time, high preparation cost and poor chemical stability.
Hollow spherical polyaniline (HSPANI) is used as the construction unit, and oxalyl chloride is used as the crosslinking agent to prepare supercrosslinking polyaniline through N-alkylation reaction, and the reaction conditions are optimized to achieve a more efficient preparation process.
The low-cost and efficient preparation of supercrosslinked polyaniline is achieved, and the resulting material has high thermal stability and good adsorption properties, which is suitable for treating organic pollutants.
Smart Images

Figure CN114957737B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material synthesis, and in particular relates to a method for preparing super-crosslinked polyaniline by utilizing N-alkylation reaction. Background Art
[0002] Hypercrosslinked polyaniline (HCPANI) is a new type of organic microporous material with a highly crosslinked structure. Since the American scientist Frantisek Svec prepared HPANI in 2007, it has been highly valued by scientific and technological workers due to its large number of microporous structures and N heteroatoms, as well as its good performance in H2 and CO2 adsorption and storage, supercapacitors and other applications. It is a research hotspot in the field of new materials.
[0003] At present, the preparation methods of hyper-crosslinked polyaniline mainly include N-alkylation method and Frediel-Crafts alkylation method. Among them, the N-alkylation method refers to the use of intrinsic or reduced linear polyaniline as a building unit, diiodomethane, diiodopropane and other highly reactive polyhalogenated alkanes or polyformaldehyde as a crosslinking agent, and the preparation is carried out in a high-temperature solvent (N,N-dimethylformamide (DMF), N,N-dimethyl sulfoxide (DMSO) through an N-alkylation reaction. In the preparation, there are disadvantages such as the high toxicity of diiodomethane and diiodopropane. In addition, in this reaction process, diiodomethane and diiodopropane have low reactivity, high reaction energy consumption (the reaction temperature is higher than 120°C), complex reaction operation, and harsh reaction conditions (the reaction requires high pressure). For example, Sharma et al. used intrinsic polyaniline, anhydrous potassium carbonate, DMF, diiodomethane, etc. as raw materials to prepare a series of hyper-crosslinked polyanilines through N-alkylation reactions (V. Sharma, A. Sahoo, Y. Sharma, P. Mohanty. RSC Adv., 2015, 5, 45749-45754; V. Sharma, S. Khilari, D. Pradhanb, P. Mohanty. RSC Adv., 2016, 6, 56421-56428). However, the above method for preparing hyper-crosslinked polyaniline has high toxicity, low reaction efficiency, high temperature, long reaction time, harsh reaction conditions, and high cost of polyaniline synthesis. Therefore, there is an urgent need for a method for preparing hyper-crosslinked polyaniline with simple operation, low cost, and mild reaction conditions.
[0004] Chinese patent document CN 107629222 A (201711098012.2) discloses a method for preparing hyper-crosslinked polyaniline, which uses polyaniline as a building unit and octavinyl silsesquioxane as a crosslinking agent to prepare hyper-crosslinked polyaniline through Friedel-Crafts alkylation reaction. However, the price of octavinyl silsesquioxane is relatively high, and the cost of the obtained hyper-crosslinked polyaniline is relatively high; in addition, the chemical stability of the obtained hyper-crosslinked porous polyaniline is relatively poor. Under strong acid / base, the Si-O-Si bond in octavinyl silsesquioxane is unstable, and chemical bonds break, causing the porous structure to collapse. In addition, the building unit polyaniline in this patent has an irregular morphology and does not contain a hollow structure, which is not conducive to the formation of a hyper-crosslinked polyaniline porous adsorption material with a regular pore structure. Summary of the invention
[0005] In order to solve the problem of low stability of existing hyper-crosslinked polyaniline, the present invention provides a method for preparing hyper-crosslinked polyaniline by using N-alkylation reaction.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The invention discloses a method for preparing super cross-linked polyaniline by using N-alkylation reaction. The method uses hollow spherical polyaniline (HSPANI) as a building unit and oxalyl chloride as a cross-linking agent to prepare the super cross-linked polyaniline by N-alkylation reaction.
[0008] Preferably, the conditions of the N-alkylation reaction are:
[0009] Under Ar protection, an acid absorbent is added to a DMF solution containing hollow spherical polyaniline and stirred to mix; then oxalyl chloride is quickly added to the reaction system and the temperature is raised to react; after the reaction, the crude product is washed, and DMF is used as a solvent, and then Soxhlet extraction is performed, and the product is dried to obtain black hyper-crosslinked porous polyaniline (HCPCs).
[0010] Preferably, the mass ratio of the hollow spherical polyaniline to oxalyl chloride is 1:0.6-0.8, preferably 1:0.65-0.75.
[0011] Preferably, the reaction temperature is 140 to 160° C., more preferably 145 to 155° C., and the reaction time is 60 to 80 h, more preferably 70 to 74 h.
[0012] Preferably, the acid absorbent for the N-alkylation reaction is anhydrous potassium carbonate, and the mass ratio of the hollow spherical polyaniline to anhydrous potassium carbonate is 1:3-5, more preferably 1:3.5-4.5.
[0013] Preferably, the N-alkylation reaction is carried out in the presence of DMF, and the amount of DMF is 75-85 mL / g hollow spherical polyaniline.
[0014] Preferably, the vacuum drying conditions are: 60° C., drying for 24 hours.
[0015] Preferably, the hollow spherical polyaniline has a rough surface morphology, an outer shell thickness of about 80-100 nm, and an inner pore diameter of about 300±5 nm. HSPANI is a mesoporous material. The specific surface area S BET 14.1m 2 g -1 The hollow spherical polyaniline is an intrinsic semi-crystalline polyaniline.
[0016] The present invention also provides a hyper-crosslinked polyaniline prepared by the above method, wherein the hyper-crosslinked polyaniline is an amorphous non-crystalline polymer, and its appearance is formed by the accumulation of nano-scale particles, and contains micropores and mesopores, wherein the micropores are mainly concentrated in 1.3-1.5nm, and the mesopores are mainly concentrated in 3-10nm; the specific surface area is 110-120m 2 g -1 .
[0017] The present invention also provides application of the super-crosslinked polyaniline in adsorbing organic dyes in water.
[0018] Beneficial effects of the present invention:
[0019] Compared with the prior art, one or more technical solutions provided by the specific embodiments of the present invention have at least the following beneficial effects:
[0020] (1) The present invention uses hollow spherical polyaniline as a building unit and oxalyl chloride as a cross-linking agent to prepare super-cross-linked polyaniline through an N-alkylation reaction, which solves the problems of high reaction temperature, complex reaction operation, long reaction time, high preparation cost, etc. in the existing super-cross-linked polyaniline preparation method, and provides a new idea for the preparation of super-cross-linked polyaniline.
[0021] (2) When the mass ratio of hollow spherical polyaniline to oxalyl chloride is 1:0.6-0.8 in the preparation of hyper-crosslinked polyaniline by the method of the present invention, the obtained hyper-crosslinked polyaniline has the largest specific surface area and the best effect of adsorbing organic pollutants.
[0022] (3) The present invention does not require special reaction equipment, expensive catalysts, or special treatment of raw materials. The reaction is simple and the reaction conditions are mild. It has the advantages of low production cost, simple process, no pollution, and easy large-scale production.
[0023] (4) The method of the present invention is to prepare a super-crosslinked polyaniline HCPCs, which is an amorphous polymer with high thermal stability and a specific surface area of 110 to 120 m 2 g -1 .
[0024] (5) The present invention uses oxalyl chloride as a cross-linking agent, which is cheap and widely available; in addition, the porous polyaniline prepared with oxalyl chloride as a cross-linking agent has good chemical stability and a stable structure under strong acid / alkaline conditions. In addition, the present invention uses a hollow spherical polyaniline with a regular morphology as a building unit, which is conducive to forming a hyper-cross-linked polyaniline porous adsorption material with a regular pore structure, thereby increasing its adsorption performance. The hollow structure can reduce the density of the hyper-cross-linked polyaniline, which is not easy to settle during the wastewater treatment process, and has a better adsorption effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the SEM image of hollow spherical polyaniline.
[0026] Figure 2 This is the infrared spectrum of hollow spherical polyaniline.
[0027] Figure 3 Schematic diagram of the synthesis route of hyper-crosslinked polyaniline HCPCs.
[0028] Figure 4 XRD pattern of hyper-crosslinked polyaniline HCPCs.
[0029] Figure 5 SEM image of hyper-crosslinked polyaniline HCPCs.
[0030] Figure 6 This is the infrared spectrum of hyper-crosslinked polyaniline HCPCs.
[0031] Figure 7 N2 adsorption isotherms and pore size distribution of hyper-crosslinked polyaniline HCPCs.
[0032] Figure 8 TGA curve of hyper-crosslinked polyaniline HCPCs. DETAILED DESCRIPTION
[0033] In order to further understand the present invention, the preferred embodiments of the present invention are further described below in conjunction with specific embodiments and drawings. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein.
[0034] Preferably, the preparation method is:
[0035] The hollow spherical polyaniline (HSPANI) used in the present invention can be prepared by the following method:
[0036] (1) Preparation of functionalized polystyrene microspheres:
[0037] Under a N2 atmosphere, acrylic acid and styrene (volume ratio of 1:9) are added to an aqueous solution containing 0.08-0.11% by mass of an initiator to obtain a mixed reaction liquid; the mixture is rapidly stirred for 15-25 minutes, and polymerization is carried out at 78-82°C. When the color of the mixture system shows a slightly blue color, the stirring rate is reduced, and the reaction is maintained until the odor of styrene disappears; the temperature is raised to 84-86°C, the reaction is carried out for 25-35 minutes, and the temperature is lowered to room temperature to obtain a functionalized polystyrene emulsion.
[0038] (2) Preparation of polystyrene@polyaniline composite microspheres:
[0039] At 0-5°C, functionalized polystyrene emulsion, deionized water and aniline are mixed to uniformly disperse the functionalized polystyrene and aniline in the solution; dilute hydrochloric acid is added until the molar concentration of HCl in the system is 0.06-0.07 mol / L; then ammonium persulfate solution is dropped into the reaction system and reacted for 10-15 hours; the product is washed, filtered and dried, namely PS@PANI composite microspheres.
[0040] (3) The PS@PANI composite microspheres were subjected to Soxhlet extraction using chloroform as solvent and then vacuum dried to obtain hollow spherical polyaniline (HSPANI).
[0041] Specifically, the initiator in step (1) is ammonium persulfate or potassium persulfate; the volume ratio of the functionalized polystyrene emulsion and aniline in step (2) is 7.5-8.5:1; and the amount of ammonium persulfate added to the reaction system is 0.02-0.03 mol / L.
[0042] Specifically, the specific preparation method of the hollow spherical polyaniline (HSPANI) used in the examples and comparative examples of the present invention is:
[0043] (11) Preparation of functionalized polystyrene microspheres:
[0044] Add 0.1g K2S2O8 and 95mL deionized water into a 250mL single-necked flask and stir to dissolve K2S2O8. Then add 0.5mL acrylic acid and 4.5mL styrene to the solution under N2 atmosphere, stir rapidly for 20min to fully emulsify the added monomers, and then polymerize at 80°C. When the color of the mixture system shows a slightly blue color, reduce the stirring rate and keep reacting until the styrene smell disappears. Subsequently, heat to 85°C, react for 0.5h, and cool to room temperature to obtain a functionalized polystyrene emulsion.
[0045] (12) Preparation of polystyrene@polyaniline composite microspheres:
[0046] At 0-5°C, 20 mL of the prepared functionalized polystyrene emulsion, 875 mL of deionized water and 5 mL of aniline were added to a 2000 mL beaker and magnetically stirred for 1 hour to evenly disperse the polystyrene and aniline in the solution. 500 mL of HCl solution (0.2 M) was added under stirring. Subsequently, 100 mL of 6.2 g of ammonium persulfate solution was dripped into the reaction system and the reaction was terminated after 12 hours of reaction. The product was washed with deionized water several times and then filtered under reduced pressure. After drying, the product was PS@PANI composite microspheres.
[0047] (13) Preparation of hollow spherical polyaniline (HSPANI):
[0048] The PS@PANI composite microspheres were subjected to Soxhlet extraction using chloroform as solvent for 48 h, and finally vacuum dried at 60 °C for 12 h to obtain hollow spherical polyaniline (HSPANI).
[0049] Figure 1 This is the SEM image of HSPANI, which shows that it has a rough surface morphology, an outer shell thickness of about 80-100nm, and an inner pore diameter of about 300nm. In the synthesis process of polystyrene spheres, a small amount of acrylic acid can act as a nucleating agent. Secondly, in the preparation process of PS@PANI, the acid groups derived from poly(styrene-acrylic acid) spheres can also adsorb aniline through acid-base interactions, so that aniline can be well assembled on the surface of poly(styrene-acrylic acid) spheres; thus, a regular and uniform hollow spherical polyaniline is obtained.
[0050] Figure 2 The infrared spectra of HSPANI, PS@PANI composite microspheres and functionalized spherical polystyrene are shown in Figure 2. Figure 2 As can be seen from the figure, for functionalized spherical polystyrene, 3570 and 3241 cm -1 The characteristic peak at 1747cm is the stretching vibration of OH. -1 The stretching vibration peak of C=O is at 1217cm -1 The results showed that styrene and acrylic acid were copolymerized and carboxyl groups were successfully introduced into polystyrene. -1 The characteristic peaks at 2912 and 697 cm correspond to the stretching vibration of CH on CH2 in polystyrene and the bending vibration of CH of monosubstituted benzene (five adjacent hydrogen atoms) in polystyrene. For PS@PANI, after polyaniline grows on the surface of functionalized polystyrene spheres, the characteristic peaks of polystyrene in its structure are reduced to 2912 and 697 cm due to the coating of polyaniline on the polystyrene spheres. -1 Most of the characteristic peaks disappeared. -1The 2912 and 697 cm-1 peaks are characteristic peaks of NH bonds. -1 The characteristic peaks of functionalized polystyrene at 1140, 1296, 1489 and 1583 cm-1 disappeared. The results of SEM and TEM image analysis showed that the functionalized polystyrene in HSPANI was completely removed by purification using Soxhlet extractor. -1 The characteristic peaks appearing at 827cm-1 are the stretching vibration of the quinone structure N=Q=N, the stretching vibration of CN, the stretching vibration of C=C on the benzene ring, and the stretching vibration of the C=N quinone ring. The results show that HSPANI is a semi-crystalline intrinsic state of polyaniline. In addition, the peak generated by the out-of-plane bending vibration of the CH bond is located at 827cm-1. -1 .
[0051] The porosity parameters of HSPANI were tested by N2 adsorption-desorption experiments at 77K and 1.0 bar. The results showed that HSPANI is a mesoporous material. BET 14.1m 2 g -1 , the pore size is about 300nm.
[0052] The octavinyl silsesquioxane of the present invention can be prepared by a conventional method by a person skilled in the art. In a preferred embodiment of the present invention, a method for preparing octavinyl silsesquioxane (OVS) is provided, and vinyl trimethoxysilane is placed in a mixed solution of acetone, hydrochloric acid and water for hydrolysis to prepare octavinyl silsesquioxane. The specific preparation method is as follows: 30 mL of vinyl trimethoxysilane is added to 150 mL of acetone, and then 80 mL of concentrated hydrochloric acid and 80 mL of water are added in sequence, reacted at room temperature for 72 hours, filtered, and the filter cake is washed with acetone and anhydrous ethanol for multiple times to obtain octavinyl silsesquioxane (OVS). Wherein, the hydrochloric acid is concentrated hydrochloric acid (mass fraction is 36%).
[0053] Using hollow spherical polyaniline (HSPANI) as the building block and acetyl chloride as the crosslinking agent, hypercrosslinked polyaniline was prepared. The schematic diagram of the synthesis route is shown in Figure 3 shown.
[0054] The present invention uses an infrared spectrometer (FT-IR) to analyze the chemical composition and structure of HCPCs. The HCPCs are subjected to infrared testing after vacuum drying. A Shimadzu UV-2600 spectrometer is used to record the absorbance of MG and RhB solutions at 617 and 554 nm. The ASAP-2460 fully automatic specific surface area analyzer is used to analyze the specific surface area and pore size distribution of HCPCs. Before the test, the HCPCs need to be degassed at 120°C for 12 hours. The pore size distribution and S BETThe nonlocal density functional theory (NL-DFT) and Brunauer-Emmet-Teller (BET) equation were used for calculation. The crystal form of HCPCs was analyzed using a Riguku D / MAX 2550 diffractometer (XRD) with a scanning range of 10-70° and a scanning rate of 0.6°s -1 The thermal stability of HCPCs was tested using a thermogravimetric analyzer (Mettler-Toledo SDTA-854) under N2 atmosphere. The TGA heating rate was 10 °C min -1 , the temperature range is 45-800 ° C. Hitachi Regulus-8220 spectrometer (SEM) was used to study the microstructure of HCPCs, and HCPCs were sprayed with gold before testing.
[0055] Example 1
[0056] The method of preparing hyper-crosslinked polyaniline using hollow spherical polyaniline (HSPANI) as a building block comprises the following steps:
[0057] Under Ar protection, 2.0 g of anhydrous potassium carbonate was added to 40 mL of DMF solution containing 0.5 g of HSPANI and stirred for 6 h. Then 166.08 μL of oxalyl chloride was quickly added to the reaction system and the temperature was raised to 150 ° C for 72 h. The crude product was filtered under reduced pressure and washed with deionized water several times to remove anhydrous potassium carbonate and unreacted monomers. Then, DMF was used as the solvent and Soxhlet extraction was performed for 48 h. Finally, it was dried at 60 ° C in a vacuum drying oven for 24 h to obtain a black hyper-crosslinked porous polyaniline polymer (HCPC-1).
[0058] Example 2
[0059] The method of preparing hyper-crosslinked polyaniline using hollow spherical polyaniline (HSPANI) as a building block comprises the following steps:
[0060] Under Ar protection, 2.0 g of anhydrous potassium carbonate was added to 40 mL of DMF solution containing 0.5 g of HSPANI and stirred for 6 h. Then 232.15 μL of oxalyl chloride was quickly added to the reaction system and the temperature was raised to 150 ° C for 72 h. The crude product was filtered under reduced pressure and washed with deionized water several times to remove anhydrous potassium carbonate and unreacted monomers. Then, DMF was used as the solvent and Soxhlet extraction was performed for 48 h. Finally, it was dried at 60 ° C in a vacuum drying oven for 24 h to obtain a black hyper-crosslinked porous polyaniline polymer (HCPC-2).
[0061] Example 3
[0062] The method of preparing hyper-crosslinked polyaniline using hollow spherical polyaniline (HSPANI) as a building block comprises the following steps:
[0063] Under Ar protection, 2.0 g of anhydrous potassium carbonate was added to 40 mL of DMF solution containing 0.5 g of HSPANI and stirred for 6 h. Then 348.23 μL of oxalyl chloride was quickly added to the reaction system and the temperature was raised to 150 ° C for 72 h. The crude product was filtered under reduced pressure and washed with deionized water several times to remove anhydrous potassium carbonate and unreacted monomers. Then, DMF was used as solvent and Soxhlet extraction was performed for 48 h. Finally, it was dried at 60 ° C in a vacuum drying oven for 24 h to obtain a black hyper-crosslinked porous polyaniline polymer (HCPC-3).
[0064] Example 4
[0065] The method of preparing hyper-crosslinked polyaniline using hollow spherical polyaniline (HSPANI) as a building block comprises the following steps:
[0066] Under Ar protection, 2.0 g of anhydrous potassium carbonate was added to 40 mL of DMF solution containing 0.5 g of HSPANI and stirred for 6 h. Then 464.3 μL of oxalyl chloride was quickly added to the reaction system and the temperature was raised to 150 ° C for 72 h. The crude product was filtered under reduced pressure and washed with deionized water several times to remove anhydrous potassium carbonate and unreacted monomers. Then, DMF was used as the solvent and Soxhlet extraction was performed for 48 h. Finally, it was dried at 60 ° C in a vacuum drying oven for 24 h to obtain a black hyper-crosslinked porous polyaniline polymer (HCPC-4).
[0067] Product performance test:
[0068] (1) HCPC-1, HCPC-2, HCPC-3 and HCPC-4 were analyzed by XRD. The results are as follows Figure 4 As shown. After HSPANI reacts with oxalyl chloride, there is only one broad diffraction peak at 2θ=21° on the XRD of HCPCs, indicating that HCPCs are amorphous non-crystalline polymers. In addition, with the increase of oxalyl chloride dosage, the diffraction peak intensity of HCPCs becomes weaker, and the results show that HSPANI reacts with oxalyl chloride.
[0069] (2) HCPCs were observed using SEM. The microstructures of HCPC-1, HCPC-2, HCPC-3, and HCPC-4 are shown in Figure 2. Figure 5 As shown in a, b, c and d, HCPCs are formed by particle accumulation. Hollow spherical polyaniline is conducive to the formation of porous hyper-crosslinked polyaniline adsorption materials.
[0070] (3) Figure 6 The infrared spectra of HSPANI, HCPC-1, HCPC-2, HCPC-3 and HCPC-4 are shown in Figure 1. After oxalyl chloride reacts with HSPANI, the infrared spectrum at 1664 cm -1A new sharp characteristic peak appears at 1296 cm-1, which is the stretching vibration peak of the C=O bond on oxalyl chloride. In addition, after the reaction of HSPANI with oxalyl chloride, the stretching vibration peak of CN on HCPCs changes from 1296 cm-1 on HSPANI to 1296 cm-1 on HCPCs. -1 Red shifted to 1255 cm -1 , and the peak is significantly broadened, indicating that the hydrogen on NH- is successfully replaced by the chlorine on oxalyl chloride. -1 The peak intensity of C=N- at 1140cm is obviously weaker than that of HSPANI. -1 The stretching vibration peak of the N=Q=N quinone structure at 827 cm also weakened, indicating that the relative content of C=N- decreased with the increase of the reaction degree of HSPANI and oxalyl chloride. The results show that oxalyl chloride reacted successfully with HSPANI, and the reaction degree was different. -1 , 1489cm -1 and 3030cm -1 They are the bending vibration peak out of the CH bond plane, the stretching vibration peak of C=C on the benzene ring and the stretching vibration peak of CH on the aromatic ring.
[0071] (4) Figure 7 The results of N2 adsorption-desorption test (77K, 1.0bar) of HCPC-1, HCPC-2, HCPC-3 and HCPC-4 are shown in the figure. It can be seen that in the low pressure range of P / P0<0.01, the adsorption amount increases linearly. In the high pressure range (0.01≤P / P0≤1.0), N2 is gradually adsorbed and a hysteresis loop appears. It can be seen that there are micropores and mesopores in HCPCs. Combined with the HCPCs in Figure 7 The pore size distribution in HCPCs shows that the micropores are mainly concentrated at 1.4 nm, and the mesopores are 3-10 nm. BET 114m 2 g -1 , while the S of HCPC-1 BET 14m 2 g -1 , S of HCPC-3 BET 42m 2 g -1 , S of HCPC-4 BET 31m 2 g -1. The reason for the low specific surface area of HCPC-1 may be that oxalyl chloride is volatile and the amount added is too small, resulting in incomplete reaction. The reason for the low specific surface area of HCPC-3 and HCPC-4 may be attributed to the following aspects: (1) The two C=O on oxalyl chloride increase the steric hindrance during the reaction, and C=O may block the pores. In addition, the polyaniline used in the present invention is in an intrinsic state, and the electron cloud density of the oxidized state part is low, and the reaction activity is weak, making the reaction difficult to proceed; (2) In the N-alkylation reaction, each amino group on the polyaniline main chain has only one reaction site, resulting in too low cross-linking density; (3) After the excess oxalyl chloride reacts with HSPANI, the unreacted acyl chloride group is converted into COOH, causing pore blocking. The above reasons lead to the small specific surface areas of HCPC-1, HCPC-3 and HCPC-4.
[0072] The obtained hypercrosslinked polyaniline in Examples 1 to 4, when the mass ratio of hollow spherical polyaniline (HSPANI) to oxalyl chloride was 1:0.5, 1:0.7, 1:1.04, 1:1.4, respectively, the S BET 14, 114, 42 and 31m respectively 2 g -1 Specific pore property data are shown in Table 1:
[0073] Table 1 Pore property data of HCPCs
[0074]
[0075] (5) Figure 8 The TGA curves of HSPANI, HCPC-1, HCPC-2, HCPC-3 and HCPC-4 were obtained under N2 atmosphere with a heating rate of 10 °C min -1 , the temperature range is 45~800℃. Different from the TGA curve of HSPANI, for HCPCs, the weight loss is clearly divided into three stages. The weight loss before 200℃ may be caused by the detachment of the proton acid doped on the HSPANI main chain, the weight loss from 200℃ to 500℃ may be caused by the cleavage of the C=O group on the cross-linking agent oxalyl chloride, and the mass loss from 500℃ to 800℃ is attributed to the degradation of the polyaniline main chain. In addition, the residual carbon rate of HCPCs is still higher than 45% at 800℃, which means that HCPCs have good thermal stability.
[0076] (6) Adsorption of malachite green (MG) / rhodamine B (RhB) by adsorbent
[0077] HSPANI, HCPC-1, HCPC-2, HCPC-3 and HCPC-4 were used to carry out adsorption experiments on dyes (MG, RhB). The adsorption conditions were as follows: adsorption time was 24 h, initial dye concentration was C0 = 200 mg L -1 , the dye volume is v = 100 mL, the adsorption temperature is T = 298 K, and the adsorbent dosage is 20 mg. The equilibrium adsorption capacity (Q e ) is 423.08 and 253.61 mg g -1 , Q of HCPC-3 to MG and RhB e 518.37 and 459.79 mg g -1 , Q of HCPC-4 to MG and RhB e 433.33 and 280.85 mg g -1 HCPC-2 had the highest adsorption capacity for MG and RhB (764.58 and 738.78 mg g -1 ). The Q of HSPANI for MG and RhB e Only 8.67 and 61.75 mg g -1 The adsorption capacity of HCPC-2 for dyes increased by more than 10 times. The π-π conjugation effect and electrostatic interaction between HCPC-2 and dye molecules helped to increase the adsorption amount.
[0078] The embodiments described above provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements and equivalent substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing hyper-crosslinked polyaniline by N-alkylation reaction, characterized in that: Hypercrosslinked polyaniline was prepared by N-alkylation reaction using hollow spherical polyaniline as building block and oxalyl chloride as crosslinking agent. The conditions of the N-alkylation reaction are as follows: under Ar protection, an acid absorbent is added to a DMF solution containing hollow spherical polyaniline, and the mixture is stirred and mixed; oxalyl chloride is quickly added to the reaction system and the temperature is raised for reaction; after the reaction, the crude product is washed, and DMF is used as a solvent, and then Soxhlet extraction is performed, and the product is dried to obtain black hyper-crosslinked porous polyaniline; the mass ratio of the hollow spherical polyaniline to the oxalyl chloride is 1:0.6-0.
8.
2. The method for preparing hyper-crosslinked polyaniline according to claim 1, characterized in that: The mass ratio of hollow spherical polyaniline to oxalyl chloride is 1:0.65-0.
75.
3. The method for preparing hyper-crosslinked polyaniline according to claim 1, characterized in that: The reaction temperature is 140~160℃ and the reaction time is 60~80 h.
4. The method for preparing hyper-crosslinked polyaniline according to claim 3, characterized in that: The reaction temperature is 145~155℃, and the reaction time is 70~74 h.
5. The method for preparing hyper-crosslinked polyaniline according to claim 4, characterized in that: The mass ratio of hollow spherical polyaniline to catalyst is 1:3-5.
6. The method for preparing hyper-crosslinked polyaniline according to claim 5, characterized in that: The mass ratio of hollow spherical polyaniline to catalyst is 1:3.5~4.
5.
7. The method for preparing hyper-crosslinked polyaniline according to claim 1, characterized in that: The acid absorbent for the N-alkylation reaction is anhydrous potassium carbonate.
8. The method for preparing hyper-crosslinked polyaniline according to claim 1, characterized in that: The volume ratio of DMF to the mass ratio of hollow spherical polyaniline is 75-85, mL / g.
9. The method for preparing hyper-crosslinked polyaniline according to claim 1, characterized in that: The hollow spherical polyaniline has a rough surface morphology, an outer shell thickness of 80-100 nm, and an inner pore diameter of 300±5 nm; the hollow spherical polyaniline is an intrinsic semi-crystalline polyaniline, a mesoporous material, and has a specific surface area S BET 14.1 m 2 g -1 .
10. The hyper-crosslinked polyaniline prepared by the preparation method according to any one of claims 1 to 9, characterized in that: Hypercrosslinked polyaniline is an amorphous polymer and a porous adsorption material. The micropores are concentrated in 1.3~1.5 nm and the mesopores are concentrated in 3~10 nm. The specific surface area is 110~120 m 2 g -1 .